2014
DOI: 10.1111/ffe.12243
|View full text |Cite
|
Sign up to set email alerts
|

Role of machining defects and residual stress on the AISI 304 fatigue crack nucleation

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It is observed that machining process generates tensile residual stress distribution in the transverse direction (360 MPa), whereas the axial residual stress fields are compressive (-394 MPa). These stresses are generated by the thermal and mechanical effects that take place at the material-tool interfaces during the material removal by turning process [28].…”
Section: Residual Stressmentioning
confidence: 99%
“…It is observed that machining process generates tensile residual stress distribution in the transverse direction (360 MPa), whereas the axial residual stress fields are compressive (-394 MPa). These stresses are generated by the thermal and mechanical effects that take place at the material-tool interfaces during the material removal by turning process [28].…”
Section: Residual Stressmentioning
confidence: 99%